PENGEMBANGAN LAPANGAN K BLOK 2 MENGGUNAKAN STUDI SIMULASI RESERVOIR DENGAN BLACK OIL SIMULATOR - Kevin William Timothy (Lembaga Penelitian Universitas Trisakti, 2015)
The objective of this thesis is to discover the development of a field using the reservoir simulationstudy based on black oil simulator. The best scenario is one with the highest recovery factoraccording to the field condition.